Hubungan Kepemimpinan Dan Ekspektasi Dengan Partisipasi Masyarakat Dalam Pembangunan Di Kelurahan Ketapang Kota Tangerang - Koswara, Deni; Mulyadi, Edi; Suhaya, Suhaya (Perspektif : Jurnal Ilmu Administrasi, 2021)
Community participation is very necessary in regional development. Research Objectives: Want to know (a). Leadership quality relationship (b). Community expectations of leadership quality (3). Community involvement in development. Method: quantitative approach with (a). Leadership variable (b). Expectation Variable (c) Dependent variable. Data collection techniques through questionnaires, surveys, documentation studies. Conclusion: (1). Leadership quality ry.1 = 0.633 > rtable (rtable = 0.195 at = 0.05 and rtable = 0.256 at α = 0.01). (2). Expected participation ry.2 = 0.602 > = 0.195 at α = 0.05 and = 0.256 in α = 0.01 (3). Community participation ry.1.2 = 0.751 > rtable = 0.195 at α = 0.05 and = 0.256 in α = 0.01). Keywords : Leadership, Expectations, Community Participation in Development